Mesoscale modelling of processing rubber-toughened acrylic polymers - Porfyrakis, K; Assender, H (2004)
The use of modelling in reproducing the microstructure of rubber-toughened acrylic polymers has been examined. A modelling procedure has been carried out in three stages. In the first stage, a rheological constitutive equation for rubber-toughened poly (methyl methacrylate) (RTPMMA) has been developed. In the second stage, the flow of RTPMMA melt has been modelled simulating common industrial polymer processing techniques such as extrusion and injection moulding. For the final stage, a mesoscale model has been built in order to reproduce the RTPMMA microstructure. Comparison with experimental observations has shown that the code has successfully predicted that rubber particle elongation is much more pronounced during injection moulding than during extrusion. It has been shown that particle elongation is greater near the walls of the mould, whereas the particles are more or less spherical in the central region of the mould. The 'shear' region (where the particles deform at an angle of approximately ±45°) has been reproduced. Particle distribution across the width and length of the mould has been found to be fairly uniform. Such a mesoscale model not only provides a better explanation of experimental observations for toughened polymers, but it can also provide the polymer industry with the ability to make useful suggestions for possible routes to improved materials for a wide range of multi-phase systems.